HUMAN RESOURCES MANAGEMENT AUDIT TO ASSESS THE EFFECTIVENESS OF EMPLOYEE AT PT. JANTI SARANA MATERIAL BETON MALANG - Johan Pande Paulo Sitorus (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This research about Management Audit based on management of HRD at PT. Janti Sarana Material Beton Malang to find out the effectiveness of human resources function. The scope of research is ten function of human resources resource which consist of: the function of human resource planning, human resource recruitment, selections and placement, training and development function, performance appraisal, the planning and career development, compensation and remuneration functions, occupational health and safety, relationship development, firing and retirement. Researcher uses descriptive qualitative analysis method. Researcher obtained data from interview, observation, and documentation. The result of research shows that from the nine functions of human resources, there are 5 ineffective human resource functions, namely human resource planning, selection, orientation and placement, training and development, performance appraisal and employee safety and health protection.Keywords: Audit Human Resource Management, Control, Effectiveness, Recommendation